PERANCANGAN SISTEM INFORMASI PENGELOLAAN APARTEMEN MUTIARA GARDEN SEMARANG BERBASIS WEB (Information Technology and Telematics, 2013)
Abstract- Mutiara Garden Semarang Apartment as one of the apartments in the city of Semarang is an apartment that is growing and continually strive to improve the standards of service and quality of the apartment from the other side of the use of information technology. During this time, the existing system of buying an apartment in the Mutiara Garden Apartments Semarang is done with conventional purchasing system and the purchase is done by recording the book so that the system needs to be addressed so everyone can access and find the desired information through the internet and can buy the apartment at a price lower compared to buying through ads or intermediaries. System development methods used in this study is SDLC consists of requirements analysis, design and implementation. System design using the Levelled DFD context diagram and consists of a Level 0 DFD, ERD and data dictionary. Creating a website using PHP programming and MySQL databaseKeywords - Real Information systems, Apartments, Mutiara Garden Semarang